1971
DOI: 10.1073/pnas.68.7.1594
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Identification of the Chromosome Carrying the IXth Linkage Group (Including H-2) in the House Mouse

Abstract: Mus poschiavinus X M. musculus hybrids, which had seven metacentric chromosomes derived from the poschiavinus complement, were repeatedly backcrossed to M. musculus and selected for the chromosome carrying the H-2 complex. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The observation that the allele T specifies an antigen on the surface of sperm is thus a needed vindication of the prediction that genes with a morphogenetic role will be found to code for components of the cell surface. It also, incidentally, supports the premise that the altered transmission ratios (13) and they may well suppress crossingover in the opposite direction; in any case the T-locus is so close to the centromere, perhaps even adjacent to the centromeric heterochromatin according to Klein (14), that even the allele T, which is not known to suppress recombination, might be expected to produce a detectable haploid effect; (b) X and Y chromosomes are thought not to undergo crossingover (12), Our results with anti-T serum are compatible with some degree of haploid influence because in cytotoxic tests considerably less than 100% of sperm from T/+ heterozygotes were susceptible to anti-T antibody, suggesting that some sperm had less or no antigen T. This interpretation is unwarranted however, as the serological system is a relatively weak one, with low antibody titers; thus there is no justification for concluding that sperm not lysed in the cytotoxic test are devoid of antigen. Furthermore, the considerations concerning the effect of crossingover on the gene content of immature sperm suggest that even where a haploid effect might be demonstrable it would be partial rather than complete.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The observation that the allele T specifies an antigen on the surface of sperm is thus a needed vindication of the prediction that genes with a morphogenetic role will be found to code for components of the cell surface. It also, incidentally, supports the premise that the altered transmission ratios (13) and they may well suppress crossingover in the opposite direction; in any case the T-locus is so close to the centromere, perhaps even adjacent to the centromeric heterochromatin according to Klein (14), that even the allele T, which is not known to suppress recombination, might be expected to produce a detectable haploid effect; (b) X and Y chromosomes are thought not to undergo crossingover (12), Our results with anti-T serum are compatible with some degree of haploid influence because in cytotoxic tests considerably less than 100% of sperm from T/+ heterozygotes were susceptible to anti-T antibody, suggesting that some sperm had less or no antigen T. This interpretation is unwarranted however, as the serological system is a relatively weak one, with low antibody titers; thus there is no justification for concluding that sperm not lysed in the cytotoxic test are devoid of antigen. Furthermore, the considerations concerning the effect of crossingover on the gene content of immature sperm suggest that even where a haploid effect might be demonstrable it would be partial rather than complete.…”
Section: Discussionmentioning
confidence: 50%
“…Selected mice yielding good antiserum were bled from the tail 7, 10, and 14 (8) is added to each tube, and the proportion of dead (stained) sperm counted in a counting-chamber. Controls consisted of tubes in which phosphate-buffered saline was substituted for either antiserum or horse serum.…”
Section: Methodsmentioning
confidence: 99%
“…According to Nesbitt (1974), the banding pattern of rat chromosome 14 is very similar, if not exactly the same, to that of mouse chromosome 17 which carries the mouse MHC locus (Klein 1971;Miller et al 1972), and on these bases, she predicted the rat MHC locus on the chromosome 14. Our data fulfil this prediction and further substantiate the current notion that the chromosome banding similarity reflects the conservation of the homologous gene in different species, as have been shown by comparative gene mapping (Human Gene Mapping 5, 1979;Garver et al 1980).…”
Section: Immunoselection Of the Hybrid Clonesmentioning
confidence: 99%
“…The search for the genetic role of the MHC has thus become a subject of special interest in recent years, and the chromosomal organization of the MHC region is predicted to be highly conservative during evolution, showing striking similarities in the mouse, rat and man (Gill et al 1978). The mouse MHC (H-2) locus has been mapped on chromosome 17 by comparative analyses of likage groups and chromosome banding patterns in some translocation stocks (Klein 1971;Miller et al 1972). …”
Section: Introductionmentioning
confidence: 99%
“…Discussion Considerable interest centers on mapping genes that code T cell receptor(s) for Ag/ L In fact finding the chromosomes that do not bear the receptor(s) is probably as significant as finding the ones that do, depending on which these turn out to be. Various theoretical and experimental considerations have suggested that in the mouse genes controlling Ag/I receptors should be found on chromosomes bearing immunoglobulin heavy chain genes and/or MHC genes, i.e., chromosomes 12 and 17, respectively (6)(7)(8)(9)(10)(11)(12)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Since on occasion Ag-binding T cell products have been shown to bear immunoglobulin idiotypes thought to be controlled by a combination of immunoglobulin light and heavy chains, chromosomes bearing light chain genes, i.e., chromosomes 6 and 16 (21,22), may also be implicated, although this is apparently not necessarily true (35).…”
mentioning
confidence: 99%